2019
DOI: 10.1002/2211-5463.12605
|View full text |Cite
|
Sign up to set email alerts
|

1‐Hydroxy‐xanthine derivatives inhibit the human Caf1 nuclease and Caf1‐containing nuclease complexes via Mg2+‐dependent binding

Abstract: In eukaryotic cells, cytoplasmic mRNA is characterised by a 3′ poly(A) tail. The shortening and removal of poly(A) tails (deadenylation) by the Ccr4‐Not nuclease complex leads to reduced translational efficiency and RNA degradation. Using recombinant human Caf1 (CNOT7) enzyme as a screening tool, we recently described the discovery and synthesis of a series of substituted 1‐hydroxy‐3,7‐dihydro‐1H‐purine‐2,6‐diones (1‐hydroxy‐xanthines) as inhibitors of the Caf1 catalytic subunit of the Ccr4‐Not complex. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…[24][25][26][27][28] Biochemical studies using the purified complex, or the isolated nuclease subcomplex also showed a differential contribution of the subunits, although evidence for allosteric regulation has also been reported. [29][30][31][32][33]21 A model based on the Xray structures of the yeast Not1(MIF4G)-Caf1-Ccr4 complex 17 and human CNOT6L 34 suggested interactions between the LRR of Ccr4 and the catalytic EEP domain and a distance of 60 Å between the tightly bound divalent metals in the catalytic sites of Caf1 and Ccr4. 17 By contrast, a recently reported structure of human Caf1/ CNOT7-Ccr4/CNOT6 shows the distance to be notably shorter (46 Å).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Biochemical studies using the purified complex, or the isolated nuclease subcomplex also showed a differential contribution of the subunits, although evidence for allosteric regulation has also been reported. [29][30][31][32][33]21 A model based on the Xray structures of the yeast Not1(MIF4G)-Caf1-Ccr4 complex 17 and human CNOT6L 34 suggested interactions between the LRR of Ccr4 and the catalytic EEP domain and a distance of 60 Å between the tightly bound divalent metals in the catalytic sites of Caf1 and Ccr4. 17 By contrast, a recently reported structure of human Caf1/ CNOT7-Ccr4/CNOT6 shows the distance to be notably shorter (46 Å).…”
Section: Introductionmentioning
confidence: 99%